Challenges to Collaboration, Inclusion and Best Practices within the Special Education Community - Scott-Croff, Cecilia (Journal of the American Academy of Special Education Professionals, 2020)
This manuscript identifies the challenges of children with special needs and their families. This text further highlights the complexity of integrating children with intellectual differences into inclusive settings. Furthermore, the author incorporates the teamwork and collaboration principles and practices of the Division for Early Childhood (DEC) of the Council for Exceptional Children (CEC, 1990). In keeping with the Council’s principles, the most important aspect of the Council’s mission and goals is to work across systems to meet the needs of children and families (DEC 2009). These principles focus on the importance of parent involvement, collaboration and interdisciplinary approaches to services. Lastly, this paper examines inclusion, advocacy and support for parents while reflectively examining a study (Scott-Croff, 2017) that details the perspectives of parents and pediatricians caring for children on the autism spectrum.